Endoscopic versus surgical management for colonic volvulus hospitalizations in the United States - Dushyant Singh Dahiya; Abhilash Perisetti; Hemant Goyal; Sumant Inamdar; Amandeep Singh; Rajat Garg; Chin-I Cheng; Mohammad Al-Haddad; Madhusudhan R. Sanaka; Neil Sharma (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Colonic volvulus (CV), a common cause of bowel obstruction, often requires intervention. We aimed to identify hospitalization trends and CV outcomes in the United States. Methods We used the National Inpatient Sample to identify all adult CV hospitalizations in the United States from 2007 to 2017. Patient demographics, comorbidities, and inpatient outcomes were highlighted. Outcomes of endoscopic and surgical management were compared. Results From 2007 to 2017, there were 220,666 CV hospitalizations. CV-related hospitalizations increased from 17,888 in 2007 to 21,715 in 2017 (p=0.001). However, inpatient mortality decreased from 7.6% in 2007 to 6.2% in 2017 (p<0.001). Of all CV-related hospitalizations, 13,745 underwent endoscopic intervention, and 77,157 underwent surgery. Although the endoscopic cohort had patients with a higher Charlson comorbidity index, we noted lower inpatient mortality (6.1% vs. 7.0%, p<0.001), mean length of stay (8.3 vs. 11.8 days, p<0.001), and mean total healthcare charge ($68,126 vs. $106,703, p<0.001) compared to the surgical cohort. Male sex, increased Charlson comorbidity index scores, acute kidney injury, and malnutrition were associated with higher odds of inpatient mortality in patients with CV who underwent endoscopic management. Conclusions Endoscopic intervention has lower inpatient mortality and is an excellent alternative to surgery for appropriately selected CV hospitalizations.